Optimal timing of thoracic radiotherapy in limited stage small cell lung cancer (SCLC) with daily fractionation: A brief report. (March 2019) - Hasan, Shaakir; White, Richard; Renz, Paul; Abel, Stephen; Otaibi, Zachary; Monga, Dulabh; Colonias, Athanasios; Wegner, Rodney E.
Summary: Survival in limited stage small cell lung cancer (LS-SCLC) improves with faster initiation of hyper-fractionated thoracic radiotherapy (TRT) following chemotherapy, however, it is unknown if this association exists for more commonly employed daily fractionated regimens. Our results suggest that this association is present even with daily fractionation.